Digital Health Interventions to Support Self-Management in Patients with Type 2 Diabetes - Yohanes Wenda; Maria Wanggai; Jonathan Kogoya (Magenta Journal De Healthymedi, 2025)
This study examines the influence of digital health interventions on self-management among patients with Type 2 diabetes mellitus in Makassar, Indonesia. A quantitative cross-sectional design was employed involving 150 adult patients who actively used digital health technologies for diabetes management. Data were collected using standardized questionnaires measuring digital intervention usage, medication adherence, self-efficacy, and glycated hemoglobin levels. Statistical analyses included descriptive statistics, Pearson correlation, multiple regression, and independent samples t-tests. The findings revealed that digital health intervention usage significantly improved medication adherence, enhanced self-efficacy, and reduced HbA1c levels. Digital engagement was identified as the strongest predictor of glycemic control. The study’s novelty lies in its integrated examination of clinical, behavioral, and psychological outcomes within the Indonesian healthcare context. These findings highlight the strategic role of digital healthcare technologies in supporting patient-centered chronic disease management and improving healthcare accessibility. The study provides important implications for healthcare institutions and policymakers in developing sustainable digital health systems for diabetes care.